Effects of supplemental zinc sulfate on growth performance, carcass characteristics, and antimicrobial resistance in feedlot heifers - Van Bibber-Krueger, Cadra L (J Anim Sci, 2019)
Effects of supplemental Zn as Zn sulfate on feedlot performance, carcass traits, and antimicrobial resistance were evaluated using 480 crossbred heifers (BW = 385 kg ± 13.08) in a randomized complete block design. Heifers were blocked by BW and randomly assigned within block to diets with 0, 30, 60, or 90 mg supplemental Zn/kg DM. Heifers were housed in dirt-surfaced pens (20 animals per pen; 6 pens per treatment) equipped with fence-line feed bunks and automatic water fountains. Heifers were fed once daily to ensure ad libitum intake. Plasma was collected on day 0 from five randomly selected heifers per pen and repeated on days 63 and 115 to determine plasma Zn concentrations. Random samples of freshly voided feces were collected from the surface of each pen the day of harvest to determine antibiotic resistance. Heifers were transported on day 144 to a commercial abattoir where hot carcass weight (HCW) and incidence of liver abscesses were recorded at harvest and HCW, dressed yield, ribeye area, 12th rib fat, quality and yield grades were recorded after 36 h of refrigeration. Plasma Zn concentration increased (P = 0.02) linearly in response to increasing concentrations of dietary Zn. Final BW and ADG were unaffected by supplementation (P ≥ 0.29). Quantified levels of resistance to ceftriaxone and tetracycline among fecal Escherichia coli were not impacted (P > 0.05) by dietary zinc concentrations. Increasing Zn concentrations tended to decrease (linear effect, P = 0.07) DMI, resulting in a linear (P = 0.03) and tendency for quadratic (P = 0.12) improvement in feed efficiency with increasing Zn concentration. No differences were detected for HCW, dressed yield, ribeye area, 12th rib fat, percentages of carcasses grading Select or Choice, or yield grade (P > 0.53), but added Zn tended to affect percentage of carcasses that graded Prime, peaking at 60 mg/kg added Zn (quadratic effect, P = 0.07). In vitro fermentations were performed using ruminal fluid cultures containing 0, 30, 60, 90, 120, or 150 mg Zn/kg substrate DM to determine impact of Zn on gas production, VFA concentrations, and in vitro DM disappearance (IVDMD). There were no effects of Zn on in vitro gas production, IVDMD, or most VFA (P > 0.15), but isovalerate decreased linearly in response to added Zn (P = 0.05). Supplementing finishing heifers up to 60 mg Zn/kg diet DM improved feed efficiency compared to other treatments.